Animal feeding stuffs: Methods of sampling and analysis. Determination of Deoxynivalenol, Aflatoxin B1, Fumonisin B1 & B2, T-2 & HT-2 toxins, Zearalenone and Ochratoxin A in feed materials and compound feed by LC-MS/MS. (16th April 2020) - British Standards Institution
No abstract available